Question

\[ f(x) = 3x + 4 \quad g(x) = 2x - 3 \] \[ \text{Find: } f \circ g(x) \]

Ask by Malone Ingram. in South Africa
Feb 22,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

f ∘ g(x) = 6x − 5

Solution

We are given the functions:   f(x) = 3x + 4   g(x) = 2x − 3 To find the composition f ∘ g(x), substitute g(x) into f(x):   f(g(x)) = 3(2x − 3) + 4 Now, simplify the expression:   = 6x − 9 + 4   = 6x − 5 Thus, f ∘ g(x) = 6x − 5.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find \( f \circ g(x) \), which is the composition of the functions \( f \) and \( g \), we need to substitute \( g(x) \) into \( f(x) \). 1. Start by finding \( g(x) \): \[ g(x) = 2x - 3 \] 2. Now substitute \( g(x) \) into \( f(x) \): \[ f(g(x)) = f(2x - 3) = 3(2x - 3) + 4 \] 3. Simplify the expression: \[ = 6x - 9 + 4 \] \[ = 6x - 5 \] Thus, \( f \circ g(x) = 6x - 5 \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy